ANALISIS RISIKO PROYEK DERMAGA APUNG DENGAN KERANGKA KERJA ISO 31000 - Abrar Adhipramana; Aditya Maharani; Irma Rustini Aju (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
The increasing number of dock needs is a business opportunity that is being utilized by a company engaged in the Modular Float System or floating cubes in East Java. The company uses a Modular Float System or floating cubes made from High Density Polyethylene (HDPE) to be structured into an environmentally friendly floating dock. However, the floating dock business based on the Modular Float System or floating cubes is still experiencing several obstacles. The constraints experienced can cause losses for the company. This research uses the ISO 31000:2018 framework to identify potential risks and determine priority risks. Then design a strategy to mitigate the risk based on the root causes of the risk. The results of the analysis using the ISO 31000: 2018 framework found 33 sub risks from 4 risk categories. Based on the Risk Assessment, there are 4 priority sub-risks. The priority sub risks from external risk category are analyzed in order to get the root causes of their occurrence to obtain the right risk management strategy for the floating dock project.